Cobra Kai. Season 4 [videorecording (DVD)] - Macchio, Ralph, 1961-; Zabka, William, 1965-; Henggeler, Courtney, 1978-; Maridueña, Xolo, 2001-; Buchanan, Tanner, 1998-; Mouser, Mary Matilyn, 1996-; Bertrand, Jacob; DeCenzo, Gianni, 2001-; List, Peyton, 1998-; Rubio, Vanessa, 1983-; Griffith, Thomas Ian; Kove, Martin (Sony Pictures Home Entertainment, 2022)
"Season 4 finds Miyagi-Do and Eagle Fang dojos joining forces to take down Cobra Kai at the All Valley Under 18 Karate Tournament... and whoever loses must hang up their gi. As Samantha and Miguel try to maintain the dojo alliance and Robby goes all in at Cobra Kai, the fate of the Valley has never been more precarious. What tricks does Kreese have up his sleeve? Can Daniel and Johnny bury their decades-long hatchet to defeat Kreese? Or will Cobra Kai become the face of karate in the Valley?" --Container.